PENGARUH STRES KERJA, MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DI KANTOR GUBERNUR JAWA TENGAH - Sandy Andalasta Al Hadad, 14.05.51.0231; Priyono, Bambang Suko (Students' Journal of Economic and Management, 2018)
This study aims to examine and analyze the effect of work stress, motivation and work environment on employee performance. The object of research in this writing is the Office of the Governor of Central Java. The sampling technique in this study was using simple random sampling technique with a total of 100 respondents. The data analysis tool used in this research is the Multiple Linear Regression Analysis, where previously Validity and Reliability were tested. The results of the research are (1) work stress has a negative and insignificant effect on employee performance, the higher the level of work stress in the employee, it will reduce employee performance. (2) Motivation has a positive and significant effect on employee performance, the higher the motivation in the employee, the employee's performance is also increasing. (3) The work environment has a positive and significant effect on employee performance, the better and more conducive the work environment conditions are to provide a comfortable sense of security and enable employees to work optimally because the work environment directly affects employee performance in completing work responsibilities, then employee performance more increasing. Keywords: Job Stress, Work Motivation, Work Environment, and Employee Performance